The impact of high school students’ enthusiasm for game-based learning (GBL) on their enthusiasm for mathematics learning - Panjaitan, M. Azhari; Dasari, Dadan (Universitas Maritim Raja Ali Haji, 2024)
The low interest of students in mathematics learning can negatively impact their academic performance. Game-based learning has been implemented to increase students' interest and enthusiasm for studying mathematics. This study aims to analyze the impact of high school students' enthusiasm for game-based learning on their enthusiasm for mathematics learning. The research uses a quantitative method through an online questionnaire distributed to 216 West Sumatra and North Sumatra high school students. Data were analyzed using binary logistic regression to understand the effect of game-based learning on students' enthusiasm for mathematics. The results show that students' enthusiasm for game-based learning through traditional and online games significantly influences their interest in mathematics learning, with a model accuracy rate of 90.7%. Additionally, the game-based learning approach boosts students' interest and facilitates collaboration and critical thinking skills. This study concludes that game-based learning is an effective method for enhancing students' enthusiasm for mathematics, and it is recommended that teachers integrate this approach into high school mathematics curricula.